Agroforestry system as alternative approach to daylighting design analyzing light transfer of selected Philippine plants for daylighting applications - Senoy, Kent Harvey B. (2020)
"Daylighting has become popular as a passive lighting method today. However, there is an insufficient amount of research pertaining to other methods and configurations in daylighting design. The study examined the potential of plant canopies as models for sun shading devices that can be used as daylighting configurations. The study has been limited on the study of plants used in agroforestry. The research utilized a descriptive and quantitative research that followed an input-process-output-outcome (IPOO) design process. The process involved the measurement of plant structure (input), 3D modelling of plant structures (process) and program simulation of light to 3D models (output). The simulation results were then used to create sun shading configurations based on the canopy structure of the plants (outcome) and were then matched to the actual lux reduction of the physical plants through multiple tests and simulation. The research was able to produce daylighting configurations that matches 85-95% of the actual lux reduction produced by the physical plants in agroforestry systems."